ACUTE PHOSPHATE NEPHROPATHY AFTER ORAL SODIUM PHOSPHATE FOR BOWEL PREPARATION IN AN ELDERLY PATIENT - Elcioglu, Omer Celal; ELÇİOĞLU, ÖMER CELAL; OZKOK, Abdullah; BAKAN, Ali; BAHAT, Kubra Aydin; Ozluk, Yasemin; Kilicaslan, Isin; ODABAS, Ali Riza (My University, 2015)
Acute phosphate nephropathy (APN) can result from oral sodium phosphate (OSP) (dibasic sodium phosphate and monobasic sodium phosphate) purgatives used for bowel cleansing before colonoscopy. Hyperphosphatemia, symptomatic hypocalcemia, hypernatremia, hypokalemia, high anion gap metabolic acidosis and acute kidney injury (AKI) are sometimes seen after OSP. Here in a case of AKI which advanced after preparation for colonoscopy with OSP is presented. The patient was a 77 year old female. She had type 2 diabetes mellitus and hypertension. A colonoscopy was performed to investigate the etiology of constipation. OSP was administered for preparation of colonoscopy and, after the procedure AKI which clinically compatible with APN developed. APN was shown with renal biopsy.